2005
DOI: 10.1021/jf050045p
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of Green Tea (−)-Epigallocatechin Gallate on 3T3-L1 Preadipocytes Depends on the Cdk2 Pathway

Abstract: This study was designed to investigate the effect of green tea catechins, especially (-)-epigallocatechin gallate (EGCG), on the apoptosis of 3T3-L1 preadipocytes. Preadipocyte apoptosis as indicated by formation of DNA fragments was induced by EGCG in dose-dependent manners. While EGCG was demonstrated to decrease Cdk2 expression and activity and increase caspase-3 activity, overexpression of Cdk2 and treatment with the caspase-3 inhibitor respectively prevented preadipocytes from induction of DNA fragmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 38 publications
8
52
0
3
Order By: Relevance
“…Since apoptosis occurs in a very structured manner, upstream molecules, such as caspases, can indicate cell death before it would be visually apparent. Caspase-3 concentrations were orders of magnitude less than the levels reported in similar cells where apoptosis occurred [12], suggesting that apoptosis was not increased by the material treatments.…”
Section: Discussionmentioning
confidence: 59%
“…Since apoptosis occurs in a very structured manner, upstream molecules, such as caspases, can indicate cell death before it would be visually apparent. Caspase-3 concentrations were orders of magnitude less than the levels reported in similar cells where apoptosis occurred [12], suggesting that apoptosis was not increased by the material treatments.…”
Section: Discussionmentioning
confidence: 59%
“…Effects of tea catechins on anti-obesity are well documented. For example, EGCg, a major tea catechin, suppressed differentiation of 3T3-L1 preadipocytes to mature adipocytes Wolfram et al, 2006) and induced apoptosis (Wu et al, 2005). In animal experiPrevention of Hyperglycemia by Black Tea Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3. According to a previous report, Hsu et al 43) demonstrated that gallic acid could induce apoptotic cell death in 3T3-L1 preadipocytes in a similar way to EGCg, 44) which results in cell population growth being correlated with antioxidant activity. Additionally, Rosso et al 45) reported that gallic acid n-alquil esters have a protective effect on targets of HOCl, a powerful oxidant, through the inhibition of its productive enzyme, MPO activity, and HOCl scavenging.…”
Section: Effect Of Gs On Renal Glucose Intracellular Glycation and mentioning
confidence: 96%